Detection of biofilm formation and antibiotic sensitive among Pseudomonas aeruginosa isolated from burn patients (Journal of the College of Basic Education, 2025)
Burns are the most destructive condition, in which the outer covering layer of the skin disappears and a scab forms, which is colonized by various opportunistic microorganisms, Pseudomonas aeruginosa is a common isolate from burn infections,leading to various pathological conditions Burn swabs were collected from patients Iraqi hospitalized at Burns Specialist Hospital in the Medical City , Baghdad, Iraq by Levene technique or syringe technique, respectively. Standard laboratory protocols for identifying P.aeruginosa were followed. The Kirby-Bauer disk diffusion method was used to test the sensitivity of the isolates to antibiotics according to CLSI 2022 guidelines. Biofilm production was accessed by microtiter plate assay.Twenty five isolates of P.aeruginosa were isolated from Iraqi burn patients. Identified by Biochemical test and Vitek 2E System.Antibiotic susceptibility test was conducted to the isolates of P. aeruginosaby using disc diffusion method to 15 antibiotics from different classes.The antibiotics resistance rate was determined as follows: Trimethoprin/sulphamethhoxazole (100%) Ceftazidime and Tobtamycin (88%), Piperacllintazobactam and Cefotaxime (72%), Cefazolin and Meropenem (60%), Cefoperazone (52%) Gatifloxacin (%) and Aztreonam(20%). Pseudomonas aeruginosa isolates have the ability to form biofilms on microtiter plates .The results showed that only 56% of P. aeruginosa isolates were strong biofilm producers. Meanwhile, 36% and 8% of the isolates were intermediate and low productive, respectively. .The production of exopolysaccharides during biofilm formation makes the condition more severe. Furthermore, continuous monitoring of this type of burn wound infection using the antimicrobial profile of the isolates is essential not only for infection control but also for empiric treatment.